Years of Lyndon Johnson : the passage of power - Caro, Robert A. (New York Vintage Books, 2012)
Four of Robert A. Caro$1 (Bs monumental The Years of Lyndon Johnson displays all the narrative energy and illuminating insight that led the Times of London to acclaim it as (3z(Bone of the truly great political biographies of the modern age.s